Transcriptomic analysis reveals pharmacological mechanisms mediating efficacy of Yangyinghuoxue Decoction in CCl4-induced hepatic fibrosis in rats - Bai, Yanming; Liang, Shuang; Zhou, Yanhao; Zhou, Bo (Frontiers in Pharmacology, 2024)
Background and purpose: As a traditional Chinese medicine formula, Yangyinghuoxue Decoction (YYHXD) is used clinically for therapy of hepatic fibrosis. The pharmacological profile of YYHXD comprises multiple components acting on many targets and pathways, but the pharmacological mechanisms underlying its efficacy have not been thoroughly elucidated. This study aimed at probing the pharmacological mechanisms of YYHXD in the treatment of hepatic fibrosis. Methods: YYHXD aqueous extract was prepared and quality control using HPLC-MS fingerprint analysis was performed. A CCl4-induced rat model of hepatic fibrosis was established, and animals were randomly assigned to six groups: control, low-dose YYHXD (L-YYHXD), medium-dose YYHXD (M-YYHXD), high-dose The HPLC-MS Joint Transcriptomic analysis revealsTranscriptomic analysis reveals pharmacological mechanisms mediating efficacy of Yangyinghuoxue Decoction in CCl4-induced hepatic fibrosis in rats